Cost Evaluation in Inventory Management: A Simulation Study Based on Python - Bencomo Murga, Francisco (2025)
This article presents the results of a research project whose objective was to design a simulation process using a stochastic-dynamic model and the Jupyter Notebook tool with Phyton programming, to understand and analyze the behavior of the costs associated with an inventory management system with stochastic demand and periodic review, in a walnut distribution company. Data was collected on inventory holding costs, shortage costs, ordering costs, warehouse capacity, delivery times and demand for the last 6 months. The results obtained revealed that, over a 3-month horizon, the operating cost presents a parabolic behavior in relation to demand, which allows identifying the optimal or equilibrium point between inventory and total average costs, depending on an uncertain demand.